2022
DOI: 10.3389/fonc.2022.793190
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Initial Time Point of Local Radiotherapy for Unresectable Lung Adenocarcinoma: A Retrospective Analysis on Overall Arrangement of Local Radiotherapy in Advanced Lung Adenocarcinoma

Abstract: Local radiotherapy (LRT) is reported to be of survival benefit for advanced non-small cell lung cancer (NSCLC) in accumulating evidence, but research on the optimal initial time point remains scarce. This IRB-approved retrospective analysis identified patients diagnosed with stage IIIb–IV unresectable lung adenocarcinoma who initiated front-line LRT at our institution between 2017 and 2020. The receiver operating characteristic (ROC) curve analyses were used to cut off the initial time of LRT (before and beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…In addition, radiotherapy may produce an abscopal effect on metastatic tumors [ 34 ]. Local radiotherapy delivered to the primary NSCLC tumor can include traditional intensity-modulated radiation therapy (IMRT) [ 35 ] or stereotactic ablative radiotherapy (SABR) [ 25 , 26 ]. Using IMRT as LCT in the treatment of advanced NSCLC has been associated with a survival benefit, and Li et al reported on IMRT use in 265 patients, with a median PFS and OS of 12.7 and 38.6 months, respectively [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, radiotherapy may produce an abscopal effect on metastatic tumors [ 34 ]. Local radiotherapy delivered to the primary NSCLC tumor can include traditional intensity-modulated radiation therapy (IMRT) [ 35 ] or stereotactic ablative radiotherapy (SABR) [ 25 , 26 ]. Using IMRT as LCT in the treatment of advanced NSCLC has been associated with a survival benefit, and Li et al reported on IMRT use in 265 patients, with a median PFS and OS of 12.7 and 38.6 months, respectively [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local radiotherapy delivered to the primary NSCLC tumor can include traditional intensity-modulated radiation therapy (IMRT) [ 35 ] or stereotactic ablative radiotherapy (SABR) [ 25 , 26 ]. Using IMRT as LCT in the treatment of advanced NSCLC has been associated with a survival benefit, and Li et al reported on IMRT use in 265 patients, with a median PFS and OS of 12.7 and 38.6 months, respectively [ 35 ]. In addition, SABR applied to the primary lung mass has shown efficacy in treating patients with oligometastatic NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates systemic treatments, which can limit the applicability of surgical methods. Depending on disease type and stage, appropriate radiotherapy methods can be selected, and conventional chemotherapy is employed in various contexts, including neoadjuvant chemotherapy, postoperative chemotherapy, and combined radiotherapy and chemotherapy ( 22 ). Research has demonstrated that platinum-based adjuvant chemotherapy significantly enhances the survival rates of patients with completely resected stage II or stage III lung adenocarcinoma, particularly when tailored to individual patients through biomarker screening ( 23 ).…”
Section: Overview Of Lung Adenocarcinoma Treated By Western Medicinementioning
confidence: 99%
“…Radiotherapy is a crucial approach in cancer treatment, utilizing radiation to target and treat tumor lesions. It is known for its localized application and wide range of therapeutic applications, offering targeted treatment options ( 22 ). However, the side effects of radiotherapy should not be ignored.…”
Section: Treatment Of Lung Adenocarcinoma With the Combination Of Tra...mentioning
confidence: 99%